Toxicity of standing milkvetch infected with Alternaria gansuense in white mice - Yang, Bo; Nan, Zhi Biao; Li, Yan Zhong (Frontiers in Veterinary Science, 2025)
IntroductionStanding milkvetch (Astragalus adsurgens) is widely distributed in the wild in Eurasia and North America and has been bred for cultivated forage in China. Yellow stunt and root rot disease caused by Alternaria gansuense is the primary disease of standing milkvetch. A. gansuense promotes the production of swainsonine in the plant. This study aimed to determine the safety of standing milkvetch that is infected with A. gansuense as forage for animals.MethodsTwo-week-old specific pathogen-free (SPF) male white mice were fed a commercial mouse feed (CMF), healthy plant feed (HPF) and diseased plant feed (DPF) for 3 or 6 weeks. We observed histological changes in the liver and kidney tissues of the mice and measured their daily feed intake, daily water intake, body weight, feed utilization, organ coefficients, and activities of serum enzymes.ResultsThe results showed that the daily feed intake of the mice that were fed DPF and HPF was significantly higher (p < 0.05) than those fed CMF at 3 and 6 weeks. The highest increase was observed in the daily water intake of the mice fed HPF (p < 0.05) followed by DPF and CMF. However, the mice fed DPF gained the least weight (p < 0.05). There was a significantly higher percentage of liver weight to body weight of the mice fed DPF (p < 0.05) than those fed HPF for 3 weeks and those fed CMF for 3 and 6 weeks. There were significantly higher levels of concentrations of alanine aminotransferase in the mice fed DPF and HPF than those fed CMF for 3 weeks (p < 0.05) and 6 weeks (p < 0.01). However, there was no significant difference in the mice fed HPF than those fed DPF. There were significantly higher of lactate dehydrogenase concentration (p < 0.001), while the blood urea nitrogen was lower in the mice fed DPF than those fed HPF and CMF at 3 weeks. There was a significantly higher percentage of numbers of lymphocytes in the blood of the mice fed DPF (p < 0.05) than those fed HPF, but the percentages of monocytes and eosinophils were significantly lower. Comparatively, there were more apparent pathological changes in the liver and kidney tissues of the mice fed with DPF than in those fed with HPF.DiscussionThese findings indicate that standing milkvetch was toxic to white mice, and infection with A. gansuense increased its toxicity. Therefore, we conclude that standing milkvetch plants infected by A. gansuense must never be used as animal feed under any circumstances. Additionally, the amount of healthy standing milkvetch fed to animals should be appropriate, avoiding long-term or excessive feeding.